Background Paper for MFD Technical Assistance to Recent Post-Conflict Countries. (Policy Papers; Policy Paper ;, 2004)
This paper provides background information to the paper 'MFD Technical Assistance to Recent Post-Conflict Countries.' The paper presents case studies on eight countries: Afghanistan, Cambodia, the Democratic Republic of the Congo, Iraq, Kosovo, Serbia, Sierra Leone, and Timor-Leste.